A Study on Meteor Head Echo Using a Probabilistic Detection Model at Jicamarca. Issue 1 (16th January 2020) - Li, Yanlin; Zhou, Qihou; Scott, Mark; Milla, Marco
Abstract: A coded long pulse is applied to the Jicamarca 50 MHz high power large aperture radar to study meteor head echoes. We develop a probabilistic detection model, which finds 25% more meteors than the commonly used signal‐to‐noise threshold method. The long code and the probabilistic approach allow us to detect over 180 meteors per minute during the dawn hours, which is several times higher than reported previously. The typical mass of the meteoroids is estimated to be about 10 −9 kg, slightly smaller than other sensitive very‐high‐frequency and ultrahigh‐frequency high power large aperture radars except the Arecibo radar. The high sensitivity allows us to observe numerous meteors in the presence of the strongest equatorial electrojet. We report and discuss the characteristics of meteor flux rate, ablation height, and velocity with a constant noise power for the first time for the Jicamarca radar. The highest average detection height is found to be near 2 a.m., instead of near 6 a.m. when the largest average velocity is observed. This is likely due to the combination of the relative large atmospheric velocity and the substantial atmospheric entry angles around 2 a.m. The observed characteristics suggest that many meteors are detected 8° off zenith despite that the full beam width is only 2.4°. Key Points: A rigorous probability model for meteor detection is developed Detection of meteors in the presence of strong equatorial electrojets allows unbiased study of meteor characteristics Many meteors are detected in the second sidelobe and beyond and enter the radar beam with a large arrival angle